2006
DOI: 10.4067/s0717-95022006000400014
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Tool for the Human Anatomy Laboratory

Abstract: SUMMARY:A multimedia program has been developed at the Departament of Human Anatomy, Medicine School of Universidad Autónoma de Nuevo León. It offers an alternative to support the traditional laboratory practice and resolve, during the dissection, the most common problems that we have already identify in our students. Some features of this program are: photography's, diagrams, information about the structures, clinical correlation and tests. All this tools were integrated in a software using Macromedia Flash. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…In the case of the use of software, prior studies have pointed out that computational models that have been accepted by students, facilitate understanding of anatomy (Inzunza & Bravo, 1999;Bucarey & Álvarez;Adamczyk et al), improve student performance (Inzunza & Bravo, 1999;Inzunza & Bravo, 2002;Adamczyk et al), and feature an additional advantage that they can be used by students not only in the classroom, but also elsewhere (Adamczyk et al). In this context, the following elements may be cited: schematic drawing software (Inzunza & Bravo, 1999;Fontelles et al), cadaverous preparations (Inzunza & Bravo, 1999;Inzunza & Bravo, 2002;Bucarey & Álvarez); those aimed at facilitating the practice of dissection (Maldonado-Zimbrón et al 2006), and a bilingual dictionary of structures and anatomical terms (Fontelles et al).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the use of software, prior studies have pointed out that computational models that have been accepted by students, facilitate understanding of anatomy (Inzunza & Bravo, 1999;Bucarey & Álvarez;Adamczyk et al), improve student performance (Inzunza & Bravo, 1999;Inzunza & Bravo, 2002;Adamczyk et al), and feature an additional advantage that they can be used by students not only in the classroom, but also elsewhere (Adamczyk et al). In this context, the following elements may be cited: schematic drawing software (Inzunza & Bravo, 1999;Fontelles et al), cadaverous preparations (Inzunza & Bravo, 1999;Inzunza & Bravo, 2002;Bucarey & Álvarez); those aimed at facilitating the practice of dissection (Maldonado-Zimbrón et al 2006), and a bilingual dictionary of structures and anatomical terms (Fontelles et al).…”
Section: Introductionmentioning
confidence: 99%
“…As result of e‐learning, anatomical teaching material can be used virtually via internet at any place and any time and a multi‐dimensional understanding for anatomy can be acquired outside the dissection hall. Comparative studies revealed that sustained success is achieved by a combination of e‐learning and cadaver dissection (Biasutto et al., 2006; Maldonado‐Zimbron et al., 2006). Our experience shows that students not only accept the possibility to study the dissection online but they also find this tool very profitable.…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto alguns pesquisadores defendem essa utilização de computadores [13], muitos educadores defendem que o ensino de anatomia utilizando o corpo dissecado é incomparável [14] [15] [16]; outros defendem a integração dos dois métodos [17] [18]. Maldonado-Zimbrón et al [19] ressaltam que algumas ferramentas de bonecos anatômicos virtuais, tais como o Visible Human Body [20], têm buscado utilizar novas técnicas, de modo a permitirem ao estudante apreciar de modo mais realista e detalhado as regiões de estudo.…”
Section: Uso De Interfaces Anatômicas Na áRea De Saúdeunclassified